Analysis of the Influence of TikTok and Qpon Digital Voucher Marketing Strategies on Consumer Purchase Decisions in Indonesia - Mellani Indriyani; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2026)
The accelerated advancement of digital technologies has led to the increasing adoption of digital vouchers as a strategic marketing tool in e-commerce. E-commerce platforms such as TikTok Shop and Qpon extensively implement price discounts and various sales promotion programs to shape consumer purchasing behavior in Indonesia. This study seeks to examine the impact of digital voucher marketing strategies, specifically price discounts and sales promotions, on impulsive buying behavior, with positive emotion serving as a mediating variable. The research is grounded in the S–O–R theory, in which digital voucher strategies function as stimuli, positive emotion represents the internal organismic state, and impulsive buying constitutes the behavioral response. A quantitative descriptive-verificative methodology was employed, with data gathered through an online survey distributed to consumers in the Jakarta region who have previously utilized digital vouchers on TikTok Shop or Qpon. The findings are expected to indicate that price discounts and sales promotions exert a positive influence. This study contributes empirical evidence regarding the significance of emotional mechanisms in the effectiveness of digital voucher-based marketing strategies.